State regulation of innovation activity of enterprises: international experience (Economics and region, 2022)
The study of international experience in regulating the innovation market allows us to conclude that the regulatory approaches in the domestic market are rigid. Thus, in particular, the EU uses many "common" (European, domestic, regional) policies to regulate innovation activities of enterprises. Part of such regulation in the EU is horizontal, but most regulatory approaches are sectoral. The general regulatory levers of innovation regulation in the European Union are analyzed. It is determined that one of the main factors of innovation regulation is the standardization of goods and services. The tendencies of development of state regulation of innovation activity in the international arena in retrospect are investigated. It is determined that the trend of state regulation of innovations is moving from mandatory to recommendation, which is based on the competition of production and economic structures. This does not apply to a number of industries that are under strict state control. The mechanisms of regulation of innovations in the sphere of production of household appliances and motor vehicles are investigated. It is substantiated that state regulation in the international arena, in particular in the EU, is moving to a new approach in innovation policy, shifting the emphasis from purely scientific research to research and innovation aimed at solving social problems. Innovations contribute to the development of entrepreneurship - an activity that allows resources to gain new economic opportunities. Most important is the release of competitiveness potential through innovation. Innovation and regulation should continue to be studied both at the horizontal and sectoral levels. It is proved that state regulation of the innovation market in developed economies, aimed at providing a favorable economic climate for the development of innovation processes, ensures the connection of science with production tasks. International experience is of some interest for the state regulation of innovation activity in Ukraine. In order to choose the right model of regulation of innovation processes, the mechanism of formation and implementation of innovation policy should be adapted to the Ukrainian realities of state regulation.
Keywords: innovation market; state regulation of innovations; high technologies; international experience of innovation regulation